The Semiotic Status of Interlingual Subtitling - Sakellariou, Panagiotis (Meta, 2012)
This article examines the question of the semiotic status of interlingual subtitling. More specifically, it will be shown that the conception of subtitling as intersemiotic translation is theoretically untenable and therefore cannot provide the basis for an adequate approach to the peculiar character of this type of audiovisual translation. The semiotic status of interlingual subtitling is essentially determined by the particular nature of the audiovisual system. Thus, a semiotic description of the audiovisual signifying processes will be offered that will allow for a conception of the semiotic status of interlingual subtitling in intertextual terms.